(untitled) (Bangladesh Journal of Animal Science, 2015)
Quality of ultra-high temperature (UHT) treated chocolate milk manufactured by different manufacturing companies of Bangladesh was evaluated. The milk samples were collected from retail shops of different markets supplied by three major dairy brands namely Aarong, Starship and Milkman. From the organoleptic tests it was found that there were no significant variation in consistency, but significant variations (p?0.05) were found in case of flavor and colour and appearance, pH and solids-not-fat (SNF) content showed insignificant difference, while significant variations at different levels (p<0.01 to 0.05) were found in all other chemical parameters like contents of total solids, fat, protein, ash and carbohydrate (mixed sugar). There was no evidence of presence of bacteria (total viable bacteria and coliform bacteria) in any of the samples. Considering all of organoleptic, chemical and microbiological properties of the samples of UHT chocolate milks, it could be concluded that Starship UHT chocolate milk was better and more acceptable followed by that supplied by Milkman. It could be suggested that to obtain quality UHT chocolate milk proper method, composition of ingredients and also the strict hygienic and sanitary measures should be followed. Bang. J. Anim. Sci. 2015. 44(2): 128-131